GTG 2019
DOI: 10.30892/gtg.24108-345
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Designing Geoportal Interfaces

Abstract: Ge eo oJ Jo ou ur rn na al l o of f TTo ou ur ri is sm m a an nd d G Ge eo os si it te es s Year X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Geoportals are used in a wide range of fields, since they are software systems able to provide access to diverse information resources to different users, granted with different attributes. (Yamashkin et al, 2019) reported a list of functional and qualitative requirements when designing geoportal solutions, ensuring the sustainable development of the global society: availability of cartographic layout, ensuring combined thematic mapping overlapping, the existence of right navigation tools for moving across the geospatial data, access to the spatial object attributes, and the chance to reach complementary information from other multimedia sources.…”
Section: Dissemination: Geoportalmentioning
confidence: 99%
“…Geoportals are used in a wide range of fields, since they are software systems able to provide access to diverse information resources to different users, granted with different attributes. (Yamashkin et al, 2019) reported a list of functional and qualitative requirements when designing geoportal solutions, ensuring the sustainable development of the global society: availability of cartographic layout, ensuring combined thematic mapping overlapping, the existence of right navigation tools for moving across the geospatial data, access to the spatial object attributes, and the chance to reach complementary information from other multimedia sources.…”
Section: Dissemination: Geoportalmentioning
confidence: 99%
“…The GeoJSON, TopoJSON and KML data formats are used to increase the efficiency of this process. In order to make effective use of GIS, it is necessary to develop a reliable and easily modifiable programming interface [12,13].…”
Section: Implementation and Project-oriented Use Ofmentioning
confidence: 99%
“…Easy access to spatial data has been provided by internet-based systems that make use of digital maps as the visual interface to geographic information. They are known by several names: (geo)spatial data platforms, GIS user interfaces [14], digital gazetteers [15], interactive maps [16], web-based geographical information systems [17], web GIS [18], interactive atlases, geoportals [19], spatial web portals [20], web mapping applications [21], geoportal interfaces [22], cartographic interfaces [23] or map services. In this paper, we call these systems "spatial data platforms".…”
Section: Introductionmentioning
confidence: 99%